The evaluation of environmental reporting by publicly listed South African banks,Evaluation of environmental reporting by listed South African banks - Oduro-Kwateng, George (Rhodes University, Faculty of Commerce, Investec Business School, 2010)
Recently, bankers have come to realise that banking operations, especially corporate lending, affect and are affected by the natural environment and that consequently, the banks might have an important role to play in helping to raise environmental standards. Although the environment presents significant risks to banks, in particular environmental credit risk, it also perhaps presents profitable opportunities. Stricter environmental regulations have forced companies to invest in environmentally friendly technologies and pollution control measures and in tum generated lending opportunities for bankers. This research examines the corporate practices of three of the four dominant banks in South Africa with respect to the environment, focusing on issues of climate change and environmental risk management by way of reporting and disclosure to all stakeholders. The emphasis on environmental reporting by South African banks has been reinforced by the latest release of the King III Report on Corporate Governance in South Africa. Global governance requires that the triple-bottom line should be applied in all corporate undertakings due to globalisation and trade liberalisation; however, the banking sector has responded poorly to the clarion call. The false view that the banks have no significant relationship with environmental degradation is being disproved. Environmental management is a huge and massive reconstruction of what has gone wrong with nature by human influence. The South African banks have had to face with the challenging tasks of reporting on the direct and mostly the indirect impacts of their environmental activities. Based on the three sampled banks which incidentally had greater percentages of the market capitalizations, the banks have fairly performed in environmental reporting. For example, Standard Bank (SA) Ltd has just signed the Equator Principles in 2007 implying corporate lending was done in 2007 without any respect to environmental impact assessments by corporate borrowers. Consequently, environmental reporting was not done to facilitate informed decision-making by stakeholders mostly shareholders and the communities where borrowers tun businesses. The objective of this research study is to investigate the extent and quantity of/voluntary environmental disclosures in the annual and sustainability reports of the banks listed on Johannesburg Stock Exchange. The periods examined were those subsequent to the release of the Exposure Draft Coalition for Environmentally Responsible Economies (CERES) Global Reporting Initiatives (GRI) issued in 1999. Using content analysis to focus on the environmental aspects, the research study compared three annual reports and three sustainability reports of 2007 year for the three sampled banks in order to evaluate reporting practices in the period surrounding this intervention. The results suggest a trend to triple bottom-line reporting and the extent and quantity of environmental information, albeit in specific categories.
Keywords: Environmental reporting -- South Africa; Banks and banking -- South Africa; Social responsibility in banking -- South Africa; Social responsibility of business -- South Africa; Environmental protection -- South Africa; Environmental economics -- South Africa; Economic development -- South Africa -- Environmental aspects; Environmental management -- South Africa; Climatic changes -- South Africa; Coalition for Environmentally Responsible Economies; Global Reporting Initiative; Standard Bank Limited; Nedbank; ABSA Bank